Identification key to the genera of adult female mosquitoes (Diptera: Culicidae) of Singapore - Yeo, Huiqing; Tan, Cheong-Huat; Chong, Chee-Seng; Lam-Phua, Sai-Gek (Zootaxa, 2019)
Accurate identification of mosquitoes is crucial for the management and control of vector species. Although Singapore is a tropical country with high mosquito diversity, there are no identification keys specific to its mosquito fauna. An illustrated identification key to the genera of the adult female mosquitoes of Singapore is presented. Twenty genera are characterized and two genera found in Malaysia, Culiseta and Topomyia, are also included. The key will aid non-taxonomically trained operational officers in adult mosquito identification. The key to the genera provides the first crucial step in the process to species identification.